420 Progression-free survival and biomarker correlates of response with BEMPEG plus NIVO in previously untreated patients with metastatic melanoma: results from the PIVOT-02 study. (9th November 2020) - Diab, Adi; Tykodi, Scott; Daniels, Gregory; Maio, Michele; Curti, Brendan; Lewis, Karl; Jang, Sekwon; Kalinka, Ewa; Puzanov, Igor; Spira, Alexander; Cho, Daniel; Guan, Shanhong; et al.
Abstract : Background: An unmet need exists for novel therapies that produce deep and durable responses in more patients with metastatic melanoma (metMEL). Encouraging clinical activity was observed with the CD122-preferential IL-2 pathway agonist bempegaldesleukin(BEMPEG) plus nivolumab(NIVO) in first-line metMEL in the phase 1/2 PIVOT-02 trial (NCT02983045 ), 1 leading to FDA Breakthrough Therapy Designation. We present updated clinical results from PIVOT-02 in first-line metMEL, and biomarkers of response. Methods: 41 patients with previously untreated stage IV melanoma (known PD-L1 status by immunohistochemistry; 28–8 PharmDx) received ≥1 dose of BEMPEG(0.006 mg/kg) plus NIVO(360 mg) q3wks; 38 patients were efficacy-evaluable (≥1 post-baseline tumor scan). Primary endpoints were safety and objective response rate (ORR; RECIST v1.1; BICR); other endpoints included PFS, OS and biomarkers. Polyfunctional strength index (PSI) of circulating lymphocytes (determined using single-cell cytokine analysis [Isoplexis]) and eosinophil count (determined from hematology analysis) at baseline and Cycle1-Day8 were analyzed using the median cut-off for correlations with ORR and PFS. Biomarkers, including CD8 + tumor infiltrating lymphocytes (TIL) and interferon-gamma (IFNg) gene expression profile (GEP), were measured in baseline tumor biopsies and analyzed for correlation with ORR and PFS. Results: At median follow-up of 25.7 months (15May2020), ORR by BICR was 53% (20/38 patients). Complete response occurred in 13/38 patients (34%): 23% PD-L1-negative (<1% tumor cell expression); 41% PD-L1-positive (≥1% tumor cell expression). Further deepening of response was observed, with 17/38 patients (45%) achieving 100% reduction in target lesions and a 79% median reduction from baseline in tumor size (previously 62%). 1 Median time to response and time to complete response was 2.0 and 7.9 months, respectively. Median PFS and OS were not reached. 2-year OS rate was 77% (95% CI: 60–87; ITT). Safety was consistent with previous reports. 1 IFNg GEP and CD8 + TIL in baseline tumor biopsies were significantly associated with ORR and PFS. Analysis of Cycle1-Day8 blood samples demonstrated significant increases in CD4 + PSI, CD8 + PSI, and eosinophils from baseline. Increased CD8 + PSI was significantly associated with higher ORR and PFS; increased eosinophils were significantly associated with higher ORR. Conclusions: BEMPEG plus NIVO was well tolerated in first-line metMEL, with durable and further deepening of responses, regardless of baseline PD-L1 status. At 25.7 months' follow-up, mPFS and mOS were not reached. Early on-treatment (Day8) increases in CD8 + PSI and eosinophils in blood were identified as non-invasive biomarkers of response that are detectable well before clinical measures of response. A phase 3 trial evaluating BEMPEG plus NIVO in first-line metMEL is enrolling(NCT03635983 ). Trial Registration: NCT02983045 Ethics Approval: The study was approved by the institutional review board of each participating site. Reference: Diab A, Puzanov I, Maio M, et al. Clinical activity of BEMPEG plus NIVO in previously untreated patients with metastatic melanoma: updated results from the phase 1/2 PIVOT-02 study. Oral presentation at SITC; November 6–10, 2019; National Harbor, MD, USA. Abstract #O35.